Why humans build up : the rise of towers, temples and skyscrapers - Craigie, Gregor (Orca timelines., 2022)
Explores the reasons humans build skyscrapers and other tall buildings, categorizing the design and construction of various structures throughout history and the world into groupings such as beauty, spirituality, and safety. Profiles the architects, highlights the buildings' unique features, and explains the why behind the design of structures such as Eastgate Centre in Harare, Zimbabwe, Djamaâ El Djazaïr in Algiers, and Tokyo Skytree. Discusses the environmental impact of tall buildings, including the ways they sustainably can serve a growing world population.